Endurance Capacities in Professional Soccer Players: Are Performance Profiles Position Specific? - Altmann, Stefan; Neumann, Rainer; Woll, Alexander; Härtel, Sascha (Frontiers in Sports and Active Living, 2020)
The aim of this study was to investigate position-specific endurance performance of soccer players. 136 professional players competing in the 1st and 2nd division in Germany were divided into the positional groups goalkeepers (GK), central defenders (CD), wingers (WI), central midfielders (CM), and forwards (FW). All players performed an incremental treadmill test with blood lactate sampling until exhaustion with the following endurance parameters being obtained: Fixed aerobic threshold (v2mmol/l), fixed anaerobic threshold (v4mmol/l), individual aerobic threshold (vLT), individual anaerobic threshold (vIAT), and maximum velocity (vmax). Results revealed significant differences between GK and all outfield playing positions for all endurance parameters (p ≤ 0.03; ES 0.87–2.19). No significant differences among outfield playing positions were evident for any of the parameters. However, trends were found in favor of the CM compared to the WI (p = 0.11; ES = 0.68) and the FW (p = 0.06; ES = 0.47) relating to vLT as well as in favor of the CM compared to the WI (p = 0.10; ES = 0.56) relating to vIAT. Findings suggest that goalkeepers possess the lowest endurance capacity compared to other playing positions. While outfield players in general showed similar endurance performance, CM seem to possess the highest aerobic capacity of all positions as indicated by all lactate-based thresholds, however, with only small to moderate ES. These findings could lead one to question the appropriateness of current endurance training regimes to prepare all players adequately for their positional match-running demands. Indeed, endurance training of players should be specific to their match-running demands. However, it remains unknown to what extent these demands are position or player specific.